2016
DOI: 10.4236/ijcm.2016.76042
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Treatment Interruption among TB Patients in Lagos Nigeria: Is There Any Need for Treatment Supporters?

Abstract: Background: This study assessed treatment interruption of tuberculosis (TB) patients managed by treatment supporters and health care workers and other predictors of treatment interruption. Methods: A descriptive cross-sectional study was conducted. Four hundred and seventy new smear positive TB patients above 14 years of age were consecutively recruited between October 1 and December 31 2012 from 34 (23 public and 11 private) directly observed treatment short course (DOTS) facilities that offered TB treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In our study, patients who had no treatment supporter were one and a half more likely to have treatment interruption compared to those who had a treatment supporter. This was consistent with the findings from Nigeria [14] and Ghana [16] which reported lower treatment interruption and better treatment outcomes among patients supervised by treatment supporters. This can be justified by the fact that the closer the treatment supporter lives to the patient, the better the treatment adherence and successful outcome [37].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, patients who had no treatment supporter were one and a half more likely to have treatment interruption compared to those who had a treatment supporter. This was consistent with the findings from Nigeria [14] and Ghana [16] which reported lower treatment interruption and better treatment outcomes among patients supervised by treatment supporters. This can be justified by the fact that the closer the treatment supporter lives to the patient, the better the treatment adherence and successful outcome [37].…”
Section: Plos Onesupporting
confidence: 91%
“…These include basic patient-related factors such as educational status, sex, alcoholism, and cigarette smoking. Moreover, the patients’ clinical characteristics such as HIV co-infection, the presence of baseline comorbid conditions, previous TB treatment history, and drug side effects were also associated with treatment interruption [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, timely drug refill is a function of the health system factors (health workers’ knowledge and skills in managing TB patients, availability of drugs, etc) and the patient’s own responsibility of monitoring their personal drug stocks. In some studies, treatment supporters (who are often relatives) who monitor drug stocks and patients swallowing prescribed medicines have been used to counteract treatment interruption [ 25 ]. A study conducted in Nigeria reported that the attitude of health workers was associated with TB treatment interruption.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TB/HIV co-infection was a significant factor in TB treatment interruption, which is consistent with studies conducted in Nigeria, London, and Kenya. 14 , 20 , 21 This could be due to drug side effects and the failure of health workers to counsel patients on the potential side effects. Tuberculosis patients who consume alcohol are at increased risk of TB treatment interruption, as also demonstrated in studies conducted in Nandi County (Kenya), South Africa and Nairobi province (Kenya).…”
Section: Discussionmentioning
confidence: 99%
“…11 The magnitude of treatment interruption is 19%, 31%, 40% and 36% in Nigeria, Kenya, Lagos (Nigeria) and Russia, respectively, but is not known in Ethiopia. 3,[12][13][14] Treatment interruption contributes greatly to Ethiopia being one of the 20 countries with the highest estimated numbers of incident multidrugresistant tuberculosis (MDR TB) cases that together contribute 87% of the global burden. 15 The emergence of drug resistant tuberculosis (DR-TB) is a challenge for global control and prevention of the disease.…”
Section: Introductionmentioning
confidence: 99%